Cover Image, Volume 20, Issue 5. Issue 5 (15th April 2018) - Mietlicki‐Baase, Elizabeth G.; Liberini, Claudia G.; Workinger, Jayme L.; Bonaccorso, Ron L.; Borner, Tito; Reiner, David J.; Koch‐Laskowski, Kieran; McGrath, Lauren E.; Lhamo, Rinzin; Stein, Lauren M.; De Jonghe, Bart C.; Holz, George G.; et al.
Abstract : The cover image, by Elizabeth G. Mietlicki‐Baase et al., is based on the Original Article A vitamin B12 conjugate of exendin‐4 improves glucose tolerance without associated nausea or hypophagia in rodents, DOI: 10.1111/dom.13222 . Abstract : The cover image, by Elizabeth G. Mietlicki‐Baase et al., is based on the Original Article A vitamin B12 conjugate of exendin‐4 improves glucose tolerance without associated nausea or hypophagia in rodents, DOI: 10.1111/dom.13222 .